2000
DOI: 10.1016/s0014-5793(00)01239-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and characterization of maurocalcine, a scorpion toxin that activates Ca2+ release channel/ryanodine receptors

Abstract: Maurocalcine is a novel toxin isolated from the venom of the chactid scorpion Scorpio maurus palmatus. It is a 33-mer basic peptide cross-linked by three disulfide bridges, which shares 82% sequence identity with imperatoxin A, a scorpion toxin from the venom of Pandinus imperator. Maurocalcine is peculiar in terms of structural properties since it does not possess any consensus motif reported so far in other scorpion toxins. Due to its low concentration in venom (0.5% of the proteins), maurocalcine was chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
99
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 26 publications
2
99
0
1
Order By: Relevance
“…In the venom mixture, there are peptides that are specialized against vertebrates, invertebrates, or active against both. Members of all three groups are well characterized and include peptides that target all of the major ion channel types such as Na ϩ , K ϩ , Cl Ϫ , Ca 2ϩ , and ryanodine-sensitive Ca 2ϩ channels (9)(10)(11)(12). The devastating potency of the venom is caused by its ability to target multiple types of ion channels simultaneously, resulting in a massive and recurring depolarization that disables or kills the prey or predator.…”
mentioning
confidence: 99%
“…In the venom mixture, there are peptides that are specialized against vertebrates, invertebrates, or active against both. Members of all three groups are well characterized and include peptides that target all of the major ion channel types such as Na ϩ , K ϩ , Cl Ϫ , Ca 2ϩ , and ryanodine-sensitive Ca 2ϩ channels (9)(10)(11)(12). The devastating potency of the venom is caused by its ability to target multiple types of ion channels simultaneously, resulting in a massive and recurring depolarization that disables or kills the prey or predator.…”
mentioning
confidence: 99%
“…Recently, maurocalcine (MCa), a novel peptide isolated from the venom of the scorpion Scorpio maurus palmatus, has been found to possess 82% sequence identity with IpTx a (27,28). MCa shares the highly basic structural domain identified in peptide A and IpTx a important for interactions with RyR1.…”
mentioning
confidence: 99%
“…MCa shares the highly basic structural domain identified in peptide A and IpTx a important for interactions with RyR1. Preliminary work has shown that synthetic MCa (sMCa) activates RyR1 channels by inducing long living subconductance states (27). Both IpTx a -and sMCa-modified channels can reversibly transit between subconductance states and fast gating states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ce peptide de 33 acides aminés fut identifié grâce à son activité pharmacologique en tant qu'activateur du récepteur à la ryanodine (RyR1) des muscles squelettiques. La cible est particulièrement originale puisqu'il s'agit d'un canal calcique intracellulaire impliqué dans le couplage excitation-contraction [6]. Ces observations avaient laissé entrevoir la possibilité que la maurocalcine devait traverser la bicouche lipidique des cellules afin d'exercer sa fonction d'activateur de canal calcique.…”
Section: Peptides De Pénétration Cellulaire Et Mécanisme D'entrée Celunclassified